Suspended solids settling and half removal time in stabilization ponds (Tunisia) - Effebi, Kôkôh; Keffala, Chema; Vasel, Jean (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2011)
Settling is one of the processes occurring in waste stabilization ponds (WSP). Part of suspended solids (SS) is removed by sedimentation but very often the efficiency of WSP is presented without making a difference between settling and biological processes. In this way the WSP is seen as a black box process. This work presents an experimental approach to the study of the removal of wastewater suspended solids in a test column in order to improve our knowledge of the settling process in ponds. These results show that the settling test in columns can be used to estimate the half removal time (t50) for the study of settling characteristics of suspended solids in wastewater stabilization ponds.The aim of this study was to determine the half removal time (t50) in anaerobic, facultative and maturation ponds, and in the influent to these ponds, at the experimental wastewater treatment plant of CERTE (Recycling and Treatment Center of Wastewater in Tunisia), by a column settling test. The experiments lasted between 15 and 120 min. The column was 2 m high with sampling systems at various depths: 40, 80, 120, 160 and 200 cm. Half-removal suspended solids time t50 was defined as the time at which 50% of SS was removed. Models derived from the scientific literature were used to interpret the experimental data. The experimental results demonstrated that higher suspended solids concentrations in the influent led to shorter t50 values and better settling.